Online hard example mining vs. fixed oversampling strategy for segmentation of new multiple sclerosis lesions from longitudinal FLAIR MRI - Schmidt-Mengin, Marius; Soulier, Théodore; Hamzaoui, Mariem; Yazdan-Panah, Arya; Bodini, Benedetta; Ayache, Nicholas; Stankoff, Bruno; Colliot, Olivier (Frontiers in Neuroscience, 2022)
Detecting new lesions is a key aspect of the radiological follow-up of patients with Multiple Sclerosis (MS), leading to eventual changes in their therapeutics. This paper presents our contribution to the MSSEG-2 MICCAI 2021 challenge. The challenge is focused on the segmentation of new MS lesions using two consecutive Fluid Attenuated Inversion Recovery (FLAIR) Magnetic Resonance Imaging (MRI). In other words, considering longitudinal data composed of two time-points as input, the aim is to segment the lesional areas which are present only on the follow-up scan and not on the baseline. The backbone of our segmentation method is a 3D UNet applied patch-wise to the images and in which, in order to take into account both time-points, we simply concatenate the baseline and follow-up images along the channel axis before passing them to the 3D UNet. Our key methodological contribution is the use of online hard example mining to address the challenge of class imbalance. Indeed, there are very few voxels belonging to new lesions which makes training deep learning models difficult. Instead of using handcrafted priors like brain masks or multi-stage methods, we experiment with a novel modification to online hard example mining (OHEM), where we use an exponential moving average (i.e., its weights are updated with momentum) of the 3D UNet to mine hard examples. Using a moving average instead of the raw model should allow smoothing its predictions and allowing it to give more consistent feedback for OHEM.